Laws and Ordinances of the Common Council of The City of Albany 127, 133-34, ch. 25, § 10 (1820) - (:unkn) unknown (My University, 1820)
That it shall not be lawful for any person to fire or set off any gun-powder, squib, rocket or fire-work, or to fire any cannon, gun or pistol in any part of the said city, within the following bounds, viz: east of the west side of Knox-street, and north, east and south by the city line;
Keywords: DISCHARGE